2007
DOI: 10.1016/j.ab.2007.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The use of hepatitis C virus NS3/4A and secreted alkaline phosphatase to quantitate cell–cell membrane fusion mediated by severe acute respiratory syndrome coronavirus S protein and the receptor angiotensin-converting enzyme 2

Abstract: The membrane fusion process mediated by severe acute respiratory syndrome coronavirus (SARS-CoV) S protein and its cellular receptor angiotensin-converting enzyme 2 (ACE2) had been reconstituted using two Chinese hamster ovary (CHO) cell lines that constitutively express these recombinant proteins separately. This system was applied to develop a quantitative measurement of cell-cell fusion using hepatitis C virus (HCV) NS3/4A protease and a secretion-blocked EGFP-4A/4B-SEAP (EGFP: enhanced green fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This may be due to the inclusion of the DEDEDEDE peptide in Iro's study. Chou et al demonstrated that the DEDEDEDE residues prior to the natural 4A/4B cleavage markedly enhanced the cleavage efficiency (6). However, we cannot exclude the possibility that there are different copy numbers of chromosomally integrated fusion reporter genes in selected reporter cell clones.…”
Section: Discussionmentioning
confidence: 94%
“…This may be due to the inclusion of the DEDEDEDE peptide in Iro's study. Chou et al demonstrated that the DEDEDEDE residues prior to the natural 4A/4B cleavage markedly enhanced the cleavage efficiency (6). However, we cannot exclude the possibility that there are different copy numbers of chromosomally integrated fusion reporter genes in selected reporter cell clones.…”
Section: Discussionmentioning
confidence: 94%
“…C2C12-SG cell line, cultured in DM did not form myotubes where as cell line C2C12-E2G [5] expressing ectodomain of Hepatitis C virus E2 protein showed normal myogenesis (SD1 Fig. 1).…”
Section: Defective Myogenic Phenotype Of C2c12-sg Cellsmentioning
confidence: 99%
“…C2C12-SG and C2C12-E2G cell lines were established as previously reported [5]. Plasmid pAM (SD1) containing Myod, PLFR, ZAKI-4R and ACE2R was transfected into C2C12-SG or C2C12 cells using lipofectamine (Invitrogen).…”
Section: Plasmid Constructs and Establishment Of Stable Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations